Highly Crystalline Mesoporous C60 with Ordered Pores: A Class of Nanomaterials for Energy Applications. (6th December 2017) - Benzigar, Mercy R.; Joseph, Stalin; Ilbeygi, Hamid; Park, Dae‐Hwan; Sarkar, Sujoy; Chandra, Goutam; Umapathy, Siva; Srinivasan, Sampath; Talapaneni, Siddulu Naidu; Vinu, Ajayan
Abstract: Highly ordered mesoporous C60 with a well‐ordered porous structure and a high crystallinity is prepared through the nanohard templating method using a saturated solution of C60 in 1‐chloronaphthalene (51 mg mL −1 ) as a C60 precursor and SBA‐15 as a hard template. The high solubility of C60 in 1‐chloronaphthalene helps not only to encapsulate a huge amount of the C60 into the mesopores of the template but also supports the oligomerization of C60 and the formation of crystalline walls made of C60 . The obtained mesoporous C60 exhibits a rod‐shaped morphology, a high specific surface area (680 m 2  g −1 ), tuneable pores, and a highly crystalline wall structure. This exciting ordered mesoporous C60 offers high supercapacitive performance and a high selectivity to H2 O2 production and methanol tolerance for ORR. This simple strategy could be adopted to make a series of mesoporous fullerenes with different structures and carbon atoms as a new class of energy materials.